2017
DOI: 10.3390/ijms18010221
|View full text |Cite
|
Sign up to set email alerts
|

Talin Modulation by a Synthetic N-Acylurea Derivative Reduces Angiogenesis in Human Endothelial Cells

Abstract: Talin is a focal adhesion protein that activates integrins and recruits other focal adhesion proteins. Talin regulates the interactions between integrins and the extracellular matrix, which are critical for endothelial cells during angiogenesis. In this study, we successfully synthesized a novel talin modulator, N-((2-(1H-indol-3-yl)ethyl)carbamoyl)-2-(benzo[d][1,3]dioxol-5-yloxy)acetamide, referred to as KCH-1521. KCH-1521 was determined to bind talin and modulate downstream signaling molecules of talin. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Studies have shown that Talin is an indispensable factor for endothelial cell-mediated angiogenesis [14]. In patients with multiple myeloma and chronic lymphocytic leukemia, Talin1 can also promote the abnormal transport of malignant B cells to the bone marrow and lymph nodes by regulating α4β1 integrin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Talin is an indispensable factor for endothelial cell-mediated angiogenesis [14]. In patients with multiple myeloma and chronic lymphocytic leukemia, Talin1 can also promote the abnormal transport of malignant B cells to the bone marrow and lymph nodes by regulating α4β1 integrin activity.…”
Section: Discussionmentioning
confidence: 99%
“…The protein Talin1 encoded by TLN1 is a focal adhesion cytoskeleton protein that binds and activates integrins, and integrins recruit other focal adhesion kinases (FAKs). Studies have shown that Talin is an indispensable factor for endothelial cell-mediated angiogenesis 14 . In patients with multiple myeloma and chronic lymphocytic leukemia, Talin1 can also promote the abnormal transport of malignant B cells to the bone marrow and lymph nodes by regulating α4β1 integrin activity.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only method of targeting talin other than siRNA is the small molecule KCH-1521, which decreases adhesion-dependent angiogenesis. KCH-1521, however, does not distinguish between talin1 and talin2 [83]. By contrast, siRNA treatments permit a distinction between talin2 and talin1.…”
Section: Discussionmentioning
confidence: 99%